Trends in 170 years of Australian plant nursery production and climatic drivers indicate a coupled response to climate change - Manuel Esperon‐Rodriguez; Brett Bennett; Sameer Hifazat; Mark G. Tjoelker (Plants, People, Planet)
Societal Impact Statement As climate change continues to drive global warming, understanding these impacts on plant nursery production is crucial for sustainable landscape management. Our study analysed 170 years of Australian nursery production, identifying trends in species composition and climate tolerance. We found a significant shift towards climate‐tolerant species since the 1940s, with substantial changes in species turnover. Our findings have broad implications for developing climate‐resilient green spaces, enhancing biodiversity and informing policy on forestry and green infrastructure. By guiding the selection of resilient plant species, this research supports more effective climate change adaptation strategies in horticulture, contributing to sustainable community development. Summary Plant nurseries influence the development, design and maintenance of landscape plantings. Climate change, however, may represent a constraint in nursery production by limiting and shaping the species produced. We assessed changes in species composition (i.e., trees, shrubs, annuals, perennials and grasses) of nursery production in Australia over the last 170 years. We hypothesised that changes in climate were reflected in the nursery production composition, with an increase in production of more climate‐tolerant species in recent decades as a coupled response to climate change. We compiled a dataset of 4807 native plant species produced in Australian nurseries since 1851 using nursery catalogues. We identified plant species considered as ‘popular’ (produced consistently through time), ‘forgotten’ (produced historically—i.e., 1851–1960) and ‘new’ (produced recently—i.e., 2022). We calculated realised climatic niches for a subset of 3079 species using four climate variables and used the 5th and 95th percentiles of these variables to determine species climatic niche breadths and climatic tolerances. We found evidence of a coupled response where nursery production composition exhibited an increase in numbers of climate‐tolerant species since 1940s to the present. We found large shifts in species composition and turnover across decades. Seven species had continual production since 1851 to the present (popular), 1038 species were historically produced until 1950s (forgotten), and 1264 species were produced in 2022 (new). Our findings can help direct future sustainable and resilient nursery production with dynamic changes in species composition to enable nurseries to keep pace with rapid climate change.